Aesthetics and seduction on "The Immediate Erotic Stages, or The Musical Erotic", by Søren Kierkegaard (2011)
Well knows, Kierkegaard’s aesthetic stage is the stage of immediate life. This life based on the lyricism and seduction, embodied also the Kierkegaard’s character of Johannes, in the The Seducer's Diary, as the Mozart´s conceptual character of Don Juan. This article attemts to demonstrate how Kierkegaard appropriates the figure of seduction in his works and thought as the factual consolidation of immediacy, and how seduction, like music, prepare the way for a transcendental, aesthetics experience: The lives in the moment.